MANUFACTURING EMPLOYEES’ BIG FIVE PERSONALITY DIMENSIONS AND THEIR RELATIONSHIP TO JOB SATISFACTION - Shiau Wei, Chan; Lim, Hui Ting (Journal of Technology Management and Business, 2017)
Earlier studies have indicated that employees’ personalities influence their job satisfaction. Thus, this study aims to examine the relationship between the Big Five personality dimensions and job satisfaction in the manufacturing industry. This study also intends to determine which personality dimension is closely related to job satisfaction. 106 employees from the manufacturing industry in Muar, Johor were selected randomly to complete the Big Five personality questionnaire (NEO-FFI-3) and Minnesota Satisfaction Scale (MSQ). The result revealed that only extraversion, openness and conscientiousness are significantly correlated to employees’ job satisfaction. Conscientiousness is the closest dimension related to job satisfaction. This quantitative study provides new empirical evidence and contributions to the manufacturing industry.